2002
DOI: 10.1016/s0038-0717(01)00164-x
|View full text |Cite
|
Sign up to set email alerts
|

A pulse-labeling experiment to determine the contribution of recent plant photosynthates to net methane emission in arctic wet sedge tundra

Abstract: A pulse-labeling experiment to determine the contribution of recent plant photosynthates to net methane emission in arctic wet sedge tundra AbstractWe conducted a 14 C pulse-labeling experiment under ®eld conditions to estimate the contribution of recent photosynthates to methane (CH 4 ) emission in arctic wet sedge tundra dominated by Carex aquatilis and Eriophorum angustifolium. The average CH 4 emission rate from plant±soil mesocosms in this study was 0.45 g C m 22 d 21. Carbon assimilated by plants via p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 41 publications
3
68
1
Order By: Relevance
“…Although less than one percent of the tracer amount had been taken up, calculated rates of CO 2 incorporation were 0.7-1.8 mmol C m −2 d −1 under vegetation, and thus in the same range as reported for arctic wet sedge tundra (King and Reeburgh, 2002). The labelling experiment demonstrated that in our peat, the rhizosphere associated respiration was mainly limited to the upper 10-20 cm.…”
Section: Respiration and Methanogenesissupporting
confidence: 82%
“…Although less than one percent of the tracer amount had been taken up, calculated rates of CO 2 incorporation were 0.7-1.8 mmol C m −2 d −1 under vegetation, and thus in the same range as reported for arctic wet sedge tundra (King and Reeburgh, 2002). The labelling experiment demonstrated that in our peat, the rhizosphere associated respiration was mainly limited to the upper 10-20 cm.…”
Section: Respiration and Methanogenesissupporting
confidence: 82%
“…CH 4 flux depends on the balance between CH 4 production, oxidation and transport. Above-ground shoot clippings not only reduced the labile C into the soil (King and Reeburgh 2002;Ström et al 2012), but also simultaneously influenced plant mediated CH 4 transport and oxidation. For instance, increased CH 4 flux due to clipping of Carex aquatilis was attributed to the removal of the resistance to CH 4 flow within plant tissues (Schimel 1995).…”
Section: Impact Of Shoot Clipping and Root Exclusion On Ch 4 Fluxesmentioning
confidence: 99%
“…Plant presence can increase soil CH 4 flux by enhancing substrate availability. There is strong evidence showing that CH 4 emission is favored by photosynthates in the form of root exudates (King and Reeburgh 2002;Dorodnikov et al 2011;Ström et al 2012). The transport of oxygen from shoots to the rhizosphere via aerenchyma can lead to the suppression of methanogenesis and oxidation of CH 4 to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A pulse-labeling experiment showed that recently-assimilated carbon was translocated to the roots and available to soil microbial community as root exudates and emitted as CH 4 quickly (King and Reeburgh, 2002). The low availability of appropriate organic substrate for methanogens caused the lack of CH 4 production from a Dutch cut-over bog remnant; peat with relatively low lignin and phenolic content, and with a low C:N, C:P and C:K ratio had a higher potential for CH 4 production (Smolders et al, 2002).…”
Section: Onset Of Methanogenesis and Magnitude Of Ch 4 Emissionsmentioning
confidence: 99%